Efektivitas Antibakteri Campuran Nanokitosan 1% dengan Berbagai Konsentrasi Ekstrak Biji Kelengkeng Terhadap Staphylococcus Aureus - Sabrina Khairunnisa; Titania Aurelya Tandra; Mellisa Sim; Florenly Florenly (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
As shown on the qualitative phytochemical examinations, longan seeds contain bioactive compounds of flavonoids, glycosides, saponins, and tannins, hence it has antibacterial potential. Whereas nano chitosan, besides having antibacterial activity, is used as a matrix for various types of drugs and plant extracts. This study aims to compare the effectiveness of nano chitosan 1% mix with longan seed extract in inhibiting the growth of Staphylococcus aureus, between 80%, 60%, and 40% concentration. Longan seed extract was prepared using the maceration method and made into various concentrations, i.e. 80%, 60%, and 40%. The nano chitosan 1% was prepared with the ionic gelation method. The two ingredients were mixed in a ratio of 1: 1. The antibacterial investigations on the different concentrations utilized the disk diffusion method. The results presented the mean inhibition power of a mixture of 80% concentration was 9.38 mm; a concentration of 60% (8.47 mm) and a concentration of 40% (7.10 mm). Statistical analysis using one way ANOVA showed the most effective concentration of the mixture in inhibiting Staphylococcus aureus was seen at 80%, where p = 0,000 (p <0.05). The results of this study indicate that increasing the concentration of longan seed extract strengthens the inhibitory power against Staphylococcus aureus. The outcome was justified as the increment in concentration of longan seed extracts lead to an increase in the number of active compounds, thereby upsurge its effectiveness in damaging Staphylococcus aureus cells.